Examining physical activity participation barriers among adults 50 years and older: a scoping review protocol. (25th November 2022) - Wingood, Mariana; Irwin, Kent E.; Bamonti, Patricia M.; Criss, Michelle G.; Harris, Rebekah; Phillips, Emma; Vincenzo, Jennifer L.; Chui, Kevin K.
Abstract: Background: Despite the benefits of physical activity (PA), 61% of adults 50 years and older do not meet the recommended levels of PA. One method of increasing PA participation is assessing and addressing PA participation barriers. Currently, no guidance on methodologies for assessing PA participation barriers exist. Objective: The primary objective of this scoping review is to map the methodologies used to examine potential PA participation barriers faced by community-dwelling adults 50 years and older. A secondary objective is to evaluate the clinimetric properties of these methodologies. Methods: This scoping review protocol is registered with Open Science Framework (https://osf.io/wd2hx ). A systematic search of the following databases will be performed: PubMed, PsycINFO, CINAHL, Web of Science, and PEDro. Included studies will 1) present either a) data on development or clinimetric properties of PA participation barrier tool (s); or b) relative risk or odds ratios of PA participation barrier(s); 2) compare PA participation barriers or PA participation barrier tool(s) to either subjective or objective measures of PA; and 3) comprise of community-dwelling participants with a mean age of 50 years and older. A two-phase blinded independent screening process will be conducted to select the included publications. Data will be extracted using a standardized form and cross-checked by the first author. A narrative summary will accompany the results presented in tables and figures. Conclusion: This scoping review will provide a comprehensive understanding of current literature and gaps related to PA participation barrier methodologies used with adults 50 years and older.